THE DEVELOPMENT OF PUPILS’ OLYMPIC VALUES: KNOWLEDGE, SKILLS, ATTITUDES - Šarkauskienė, Asta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Objective: The aim of this study was to investigate the knowledge, skills, and attitudes of 5th grade pupils regarding Olympic values. Methods: A qualitative study using the survey method was conducted from January until March, 2019. The participants of this study were 416 fifth grade pupils (49.0 % girls), ranging from 11 to 12 years old, from seven randomly selected general education schools in Klaipeda County (Lithuania). The questionnaire design was considered suitable for discovering the range of knowledge, skills and attitudes about Olympic values. The survey was created and pilot tested internally. The final version contained 35 questions, including five demographic questions and 30 questions related to the Olympic values. Results: The Olympic value, which was found to be the most developed, is Friendship: which is at a high level. The Olympic values of Excellence and Respect both were at an average level. The worst results were with the Olympic value of Fair Play. Conclusion: Pupils have a high level of knowledge of Olympic values (Excellence, Respect, Friendship, Joy of Effort, and Fair Play), but have poorer results regarding their skills and attitudes. The level of attitudes towards the Olympic value of Fair play is low.